VERBAL AND VISUAL REPRESENTATION OF MEN IN NIVEA FOR MEN PRINT ADVERTISEMENTS - Puspadewi, Dinnawaty Annisa (2013)
The research paper is entitled Verbal and Visual Representation of Men in Nivea for Men Advertisements. It is aims to investigate the verbal and visual representation of men in Nivea for Men print advertisements and the ideologies behind the representation. The present study is largely qualitative using the frameworks of Critical Discourse Analysis proposed by Fairclough (1995) and Visual Theory by Kress and van Leeuwen (1990). The data include six Nivea for Men print advertisements that were released in 2008 until 2012. The analysis of verbal texts focuses on transitivity, inclusion and exclusion of elements of social events, and concreteness or abstraction of representation of social events. Meanwhile, mood, subjectivity, social distance, and modality analyses are employed in exploring the visual texts. The result of the study reveals that Nivea for Men print advertisements portray men as active, confident, and attractive. The men in Nivea for Men advertisement was also show their feminine side. It is also found that the ideologies underlying the representation are consumerism and metrosexuality. Keywords: representation, verbal text, visual text, print advertisements, and ideology.